Discrimination due to Pregnancy and Maternity in Organizations: Systematic Review of the Literature (Challenges of the Future, 2022)
Discrimination due to Pregnancy and Maternity in Organizations: Systematic Review of the Literature Background and originality: The purpose of this systematic review of the literature is to verify the existence of discrimination against pregnant women and mothers in the workplace and at the same time to investigate in what form and to what extent it is present. A review of the legal regulation of the mentioned field and a review of the regulation of the protection of pregnant women and mothers will also be prepared.Method: A systematic review of the literature in the following databases was performed: ProQuest, Scopus, SpringerLink, ScienceDirect, Cobiss, dLib, Google Scholar, Emerald, Hein Online and mEga search engine NUK. We focused on reviewing the literature in the period from 2011 to 2022, but because we also wanted to gain insight into how discrimination against pregnancy and motherhood in organizations changes over the years, we also included older literature in our study, for which we assessed that it will offer an in-depth insight into a better understanding of all the challenges in this area.Results: Based on the criteria for inclusion and exclusion, 42 articles published in Slovene (16) and English (26) in the mentioned study period were included in the systematic review of the literature. We found that discrimination in pregnancy and maternity is present in organizations, despite the fact that it is officially prohibited by a number of laws and regulations. It manifests itself in different forms (discrimination in employment, workplace) and in different periods (pregnancy and / or motherhood).Society: With this systematic review of the literature, we want to contribute to the social understanding of gender equality and raise awareness that pregnancy and motherhood should not be the cause of any form of discrimination in the workplace.Limitations / Future research:. In order to carry out future research, we propose to upgrade the present research with an in-depth insight into the mentioned issue through the perception of organizations. It would also make sense to investigate whether and to what extent decisions based on the Family-Friendly Company certificate issued by the Equilibrium Institute are being implemented, and what contribution this title makes in the context of reduced discrimination during pregnancy, maternity and parenting in general, the certificate represents to the employees. At the same time, we believe that it would be advisable to investigate in more detail in which segments of organizations such cases of discrimination occur more often, and consequently it would be advisable to consider more targeted measures. Key words: discrimination, pregnancy, motherhood, organization, rights, equality, law
Keywords: discrimination; pregnancy; motherhood; organization; rights; equality; law